‘People-centered approaches’ for the Kamestisuhan District of Malolos, Philippines: Involvement of local communities in long-term conservation and co-management - Mundo-Angeles, Ana Neliza del; Bautista, Patria S.; Ricafort Jr., Godofredo S.; Gopez, Ma. Teresa V, (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The research aims to show local residents of Malolos that reviving the Kamestisuhan District will bring benefits to the province and will demonstrate heritage’s meaning to society by engaging participants to assess people-centered approaches hoping to result in gaining support from them for its on-going use and protection. The study utilized a mixed method research design, specifically interview guide and survey, to gain local understanding of needs and opportunities of 11 conservation practitioners, 65 Bulakenyos from different localities wherein the majority are from Malolos, and 55 college students from Bulacan State University in Malolos. The results of this research show that the Kamestisuhan District of Malolos should be protected as a heritage site to maintain its identity and culture because raising awareness of cultural heritage can also open opportunities for bigger tourism plans and livelihood for locals. Media such as TV, documentaries, social media, radio, journal publications, and film can be used to raise awareness about heritage conservation. Modern media can create a more solid foundation for building the image and popularity of the district. This study concluded that stakeholders of heritage conservation believe they can effectively raise awareness about the importance of heritage if they have sufficient knowledge and money to spread information, research and promotion, conduct seminars, and engage in information campaigns.